Studi Fenomenologi: Peran Parenting Dalam Praktik Pemberian Gizi Balita Di Tengah Intervensi Program Pemerintah Cegah Stunting - Samta, Soraya Rosna; Lestari, Budi Dyah; Furi, Atika Zahra (Indonesian Journal of Health Community, 2025)
Stunting is a chronic nutritional problem that is still a public health challenge in Indonesia. This study aims to explore the role of parenting in toddler nutrition practices amidst the implementation of government programs to prevent stunting in Candi Village. This phenomenological study involved 15 parents of toddlers selected by purposive sampling. Data collection was conducted through in-depth interviews and participatory observations for 6 months. Data analysis used the colaizzi approach with triangulation of sources and methods. The results of the study identified five main themes: (1) parents limited understanding of toddler nutrition, (2) traditional feeding practices versus program recommendations, (3) gender roles in parenting and nutritional decision-making, (4) the influence of extended family social support, and (5) adaptation to government program interventions. The findings indicate that although government programs have been implemented, parenting practices in providing nutrition are still influenced by complex cultural, economic, and social factors. This study recommends a more holistic intervention approach by considering the local context and involving all family members in nutrition education.